The Dutch East Indies Colonial Government Efforts to Eradicate Pirates Based on the 19th Century Colonial Newspapers - Wiryandara, Hikmana Arafah (Journal of Maritime Studies and National Integration, 2024)
The presence of pirates in the waters of the Indonesian Archipelago had disturbed sailors and traders long before the arrival of the Europeans. This paper aims to show how seriously the Dutch East Indies Government faces the issue of pirates. News articles in the 19th century colonial newspapers contained considerable information about pirates in the Dutch East Indies, starting from the identities of various pirate groups and piracy cases to the Dutch East Indies Government's response to the rampant disturbances committed by the pirates. Historical methods used to examine sources include 19th century colonial newspapers, colonial archives, and previous studies and literature. This paper found that the Dutch East Indies Colonial Government made endless efforts, such as patrolling and chasing pirates, involving local nobles in the campaign against pirates, giving awards to those who played a role in pursuing and eradicating pirates, severe penalties for pirates, and the existence of cooperative efforts with the British colonies, illustrates how serious the pirates issue faced by the colonial government.